Consequences of altering stroke parameters in front crawl swiming and its simulation - McArdle, D.; Reilly, T. (Biomechanics and Medicine in Swimming. Swimming Science VI, 1992)
The aim of the study was to examine the effect of altering the normal stroke parameters in front crawl swimming. Seven club swimmers completed a series of 366 m free style trials at five different stroking rates ranging from very slow to very fast. A clear 'inverted U' pattern was observed between stroke frequency and swim velocity; the optimum stroke rate (S0 ) freely chosen by the subject producing the highest swim velocity. Pfuach subject then simulated the front crawl arm action on a swim bench using the five stroke frequencies determined during the pool tests. These were conducted at three different levels of exercise intensity. Oxygen uptake (V0 2 ), VE and heart rate were affected by changes in stroke rate at all intensities. Mean power per stroke varied according to an inverted U curve; the correlation between mean power at S t and maximum swimming velocity was 0.88 (P < 0.01) at the high~~t level of exercise. Total power output at S . was also related to swimming performance (r = 0.85; P < 0.01). 0 M~ximum swimming velocity was not significantly related to vo2 peak measured either on the swim bench or during arm cycling. Results suggest that analysis of responses to varying stroke parameters, particularly power output, may have more relevance for the swimmer than VO peak measured in a dry-land test.